The Crossed-leg Position Increases the Dimensions Within the Acoustic Target Window for Neuraxial Needle Placement in Term Pregnancy: A Prospective Observational Study. Issue 3 (September 2021) - Sharma, M.; Qasem, F.; Sebbag, I.; Jones, P.M.; Singh, S.I.
Abstract : ( Int J Obstet Anesth . 2020;44:106–111) Anatomic changes associated with pregnancy may render conduct of neuraxial procedures in parturients more difficult. The standard position for a neuraxial block requires a patient to sit on a bed with the spine flexed and legs supported on a stool, but spinal flexion may be improved by instead sitting cross-legged on the bed. Given the lack of prospective studies on this topic, the aim of this study was ultrasonographic assessment of the paramedian target area's size when a pregnant woman sits in the cross-legged position (CLP) for neuraxial needle placement compared with standard sitting position (SP). The authors hypothesized that a CLP would increase the measured lengths of the posterior longitudinal ligament (PLL) indicating an improved acoustic window between vertebrae.